Tawaghat landslide of Kuman Himalaya, India - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
Reports of lansdlide and sinking stc., at Tawanghat and its surrounding areas have been reported in past also with noticeable amount of loss of lives properties.A Sizable landslide accured in this region in december, 1962.During august 1977, a major landslide came roaring down the main nala (a local term used for small channels or stream) of Khela village and destroyed sheds and houses, killing 44 persons and 76 heads of cattle.About 150 acres of standing crops were washed out.Geological and geomorphological investigataion showed that a large area was dislocated at the head of the nala moving down the gradient and activating the boulder filled nala.The mass of the mountain scree that moved was perhaps resting already at a critical angle and the torrential rains had triggered the flow.In August, 1979 again a major gravitational slide of the steep mountainslopes between Rauntigad and tawaghat region had accured, seriously affecting Sinsa, gachila and Syankuri village situated on the above slipes.